(untitled) (Revista de Ciências Agroveterinárias, 2011)
The use of swine manure as fertilizer is the main method for final disposal of this waste. However, the dose applied must not exceed the reception capacity of the soil, to avoid the excess of elements that have potential pollutants, particularly P, Cu and Zn. In order to evaluate changes in chemical attributes of a South Brazilian Oxisol, caused by six annual applications of swine manure at the rates 0 (control), 25, 50, 100 and 200 m3 ha-1, soluble fertilizer, and manure supplemented with soluble fertilizer, a field experiment was conducted in Campos Novos, SC, in the period from 2001 to 2007. Each year, successive crops of corn (Zea mays) and oat (Avena strigosa) were grown under no-tillage. In August 2007, the soil was sampled at depths of 0-2, 4-6, 9-11, 19-21, 29-31 and 39-41 cm. Compared to the control treatment, the manure did not affect the pH and concentration of exchangeable Al and Mg, but it increased the exchangeable Ca, although only at the rate of 200 m3 ha-1, at 0-2 and 4-6 cm depths. At the first depth, soluble fertilizer decreased the pH in relation to other treatments, and at 4-6 cm depth the soluble fertilizer decreased this attribute only in relation to manure applied at the highest dose. The manure in doses of 100 and 200 m3 ha-1 increased significantly the content of extractable P at depths 0-2 and 4-6 cm, including in relation to soluble fertilizer. At the highest dose applied, the manure also raised the extractable K at all depths, while at the dose 100 m3 ha-1, this increase was observed up to 29-31 cm depth; and at the dose 50 m3 ha-1, it reached 4-6, 9-11 and 19-21 cm depths. In doses from 50 m3 ha-1, the manure increased the content of soil extractable Cu and Zn in depths of 0-2 and 4-6 cm and for doses from 100 m3 ha-1 this increase was also seen at 9-11 cm depth.